NIR luminescent nitrate bridged bimetallic phase change material with switchable dielectric constant as well as preparation method and application of NIR luminescent nitrate bridged bimetallic phase change material
By developing a NIR luminescent nitrate bridged bimetallic phase change material with a dielectric constant switchable dielectric constant, the compound structural formula is (MQ)5 [K2Nd2(NO3)13], the challenges of existing dielectric materials in terms of structural diversity and tunability are solved, the dielectric response and NIR luminescence properties are achieved, and good fatigue resistance is maintained.
Patent Information
- Application Number
- CN202411749078.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-19
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-11
AI Technical Summary
Existing dielectric materials have challenges in structural diversity and tunability, especially in the study of materials that have both dielectric constant switching and near-infrared luminescent characteristics, there are problems of structural rigidity and stability.
A NIR luminescent nitrate bridged bimetallic phase change material with a switchable dielectric constant was developed. The compound structure formula is (MQ)5 [K2Nd2(NO3)13]. By synthesizing this material, the dielectric response and NIR luminescence properties are achieved using components such as quinine ring and neodymium ions.
This material realizes the switchability of the dielectric constant during the temperature change process, maintains good fatigue resistance, and has near-infrared light emission characteristics. It is suitable for switches, sensors, actuators and other applications in smart devices.
Smart Images

Figure CN119798288A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of compatible dielectric transition and near-infrared (NIR) luminescent materials, and in particular relates to a NIR luminescent nitrate-bridged bimetallic phase change material with switchable dielectric constant, and a preparation method and application thereof. Background Art
[0002] Stimuli-responsive materials have been widely studied as a basic scientific concern. As a class of modern materials, they have switchable physical properties and have potential applications in thermal, electronic and optical industries. Among them, responsive media with switchable dielectric constants and luminescent properties are mainly concentrated on rare earth doped inorganic perovskites. This is mainly due to the following two considerations: 1) The perovskite structure easily induces significant dual dynamic properties and switchable dielectric constants; rare earth ions have unique optical properties, enabling them to emit light in a wide spectral range (from ultraviolet, visible light to near infrared). Optoelectronic materials that combine switchable dielectric constants and luminescent properties can be used in fields such as rewritable information storage, data communications and optoelectronic devices. However, the research on optoelectronic materials that combine switchable dielectric constants and luminescent properties is limited to their inherent structural rigidity, and their structural diversity and tunability remain a challenge.
[0003] In recent years, hybrid perovskites have shown great advantages in realizing soft multifunctional stimuli-responsive materials. The use of organic groups increases the flexibility of their molecular design and adaptability in different fields, greatly expanding the application range of stimuli-responsive materials. For example, 2+ and / or Cd 2+ The hybrid multifunctional stimuli-responsive material exhibits a significant dielectric constant change and strong photoluminescence, but the Mn-doped 2+ The compound is easy to absorb moisture during the preparation process, resulting in unstable structure; doping Cd 2+ The compounds have poor reversibility and unstable repeatability under the stimulation of external conditions (temperature, light, electricity, force). In addition, rare earth luminescent materials are an important part of the luminescence field. 3+ The responsive dielectric has excellent luminous efficiency and thermal stability. 3+ 、Pr 3+ 、Sm 3+ 、Eu 3+ or Dy 3+ hybrid double perovskite, and has made a breakthrough in realizing rare earth luminescent hybrid dielectric materials with switchable dielectric constants, making them the next generation of multifunctional materials.
[0004] Switchable physical / chemical properties are the main features of stimulus-responsive or smart materials. As one of the basic components in the electrical and electronic industries, dielectric materials are widely used as capacitors. Dielectric materials with low or high dielectric constants ε' act as ultra-low dielectrics in integrated circuits and as high dielectrics in energy storage and device miniaturization, and are therefore very important. However, responsive dielectrics with switchable dielectric constants have been less explored. Rare earth ions have rich optical properties. Hybrid rare earth materials with switchable dielectric constants emit light in the visible light region. In recent years, the near-infrared luminescence of rare earth complexes has attracted increasing attention and research due to its unique advantages in optical communications, infrared imaging, biomarkers and other fields. However, there are very few related reports. Summary of the Invention
[0005] Purpose of the invention: In order to solve the above-mentioned technical problems, the present invention aims to provide a NIR-luminescent nitrate-bridged bimetallic phase change material with switchable dielectric constant. The material has the properties of dielectric response and NIR luminescence. During the temperature change process, the dielectric switchability is achieved and good fatigue resistance is maintained, enriching the family of dielectric materials. Luminescence characteristics can also be achieved in the near-infrared region. These characteristics enable it to be used as switches, sensors, actuators, etc. in smart devices, providing new materials for NIR emission-responsive dielectric optoelectronic applications.
[0006] The present invention also provides a preparation method and application of the NIR luminescent nitrate-bridged bimetallic phase change material with switchable dielectric constant.
[0007] Technical solution: In order to achieve the above purpose, the present invention provides a NIR luminescent nitrate-bridged bimetallic dielectric material with switchable dielectric constant, wherein the NIR luminescent nitrate-bridged bimetallic dielectric material mainly comprises a dielectric constant having a structure of (MQ)5[K2Nd2(NO3) 13 ] compounds, wherein MQ (N-methylquinuclidine cation) is monovalent, Nd (neodymium) is trivalent, K (potassium) is monovalent, and NO3 (nitric acid) is monovalent.
[0008] Wherein, the compound is light purple block crystal.
[0009] The compound belongs to the monoclinic space group P21 / n at 153K, and the cell parameters β=93.6825(18)°; at 300K, it crystallizes in the monoclinic space group P2 / m, with unit cell parameters of β=101.914(4)°。
[0010] Among them, the compound shows an obvious dielectric transition between the low state and the high state in the temperature range of 130K to 240K, corresponding to an order-disorder structural phase transition, and also has near-infrared luminescence at 1068nm with a fluorescence lifetime of 1.920μs; the material has the properties of dielectric response and NIR luminescence.
[0011] The method for preparing the NIR luminescent nitrate-bridged bimetallic dielectric material with switchable dielectric constant according to the present invention comprises the following steps:
[0012] a) mixing quinuclidine and CH3I with ethyl acetate as solvent, filtering, drying, adding nitric acid to oxidize the I ions in the product, heating and subliming to remove the I ions, and obtaining MQ;
[0013] b) assembling MQ, neodymium nitrate hexahydrate, potassium chloride, and nitric acid, and using deionized water as a solvent;
[0014] c) heating the clear solution obtained in step b) to slowly evaporate the solvent, thereby obtaining the compound as light purple block crystals.
[0015] Further, MQ, Nd(NO3)3·6H2O and KCl were dissolved in deionized water, mixed and evenly stirred by adding nitric acid, and finally deionized water was added. The mixture was placed on a hot plate to grow crystals, which reduced the rate of crystal precipitation and improved the crystal quality. After about 2-3 days, light purple single crystals were precipitated, which were collected and dried to obtain (MQ)5[K2Nd2(NO3) 13 ].
[0016] The molar ratio of MQ, Nd(NO3)3·6H2O, KCl and HNO3 is 5:2:2:5.
[0017] The dielectric switch type NIR luminescent nitrate bridged bimetallic dielectric material of the present invention is used in dielectric switch materials, sensors, actuators and capacitors with switchable dielectric response characteristics.
[0018] Application of the dielectric switch type NIR luminescent nitrate bridged bimetallic dielectric material of the present invention in NIR luminescent materials.
[0019] The dielectric switch type NIR luminescent nitrate bridged bimetallic dielectric material of the present invention is used in information storage, data communication and optoelectronic devices.
[0020] The dielectric switch type NIR luminescent nitrate bridged bimetallic dielectric material of the present invention is used in the preparation of electrical and electronic component materials having both switchable dielectric response characteristics and NIR luminescence.
[0021] The present invention prepares Nd3+ Nitrate-bridged hybrid bimetallic dielectric (MQ)5[K2Nd2(NO3) 13 ], the compound undergoes reversible structural phase transition at 190 / 175K (heating / cooling), and X-ray diffraction analysis at different temperatures shows that the three-dimensional perovskite structure with oriented MQ in the anion cage ensures the phase transition. Due to the change in the motion of the molecular dipole, this causes ε' that can be switched between the low dielectric state and the high dielectric state. More importantly, the compound has near-infrared luminescence characteristics, Nd 3+ ions act as activators for near-infrared luminescence. This discovery helps us understand the origin of the switchable dielectric properties of hybrid rare-earth double perovskites and facilitates further exploration of their optoelectronic properties.
[0022] The compound prepared by the present invention has the structural formula: (MQ)5[K2Nd2(NO3) 13 Due to the reversible structural phase transition mechanism of the compound, X-ray single crystal diffraction experiments were carried out at 153K and 300K. At 153K, the compound belongs to the monoclinic space group P21 / n, and the cell parameters β=93.6825(18)°. At 300K, the compound crystallizes in the monoclinic space group P2 / m with unit cell parameters of β=101.914(4)°. This compound is a three-dimensional nitrate-bridged hybrid bimetallic perovskite, and its three-dimensional structure is similar to the common A2B I B III X6 is different, its molecular formula is A 2.5 B I B III X 6.5 The compound exhibits a clear dielectric transition between the low and high states in the temperature range of 130K to 220K, corresponding to the order-disorder structural phase transition. max / ε' min The ratio is as high as 1.88, ε' max As high as 1.18 times that of silicon nitride. In addition, at a frequency of 1MHz, after multiple ε' switching cycles, the dielectric constant is max and ε' min The reversibility of switching between the two states is not significantly weakened, which gives the material good thermodynamic stability. It is worth noting that the compound also emits near-infrared light at 1068nm, with an indirect band gap (Eg) of 2.96eV and a fluorescence lifetime of 1.920μs.
[0023] The method of the present invention synthesizes light purple bulk crystals with compatible dielectric transition and near-infrared (NIR) luminescence through a simple volatile solvent reaction. The high-multiplier dielectric response caused by the ordered-disordered structural phase transition of the compound can still have dielectric sensitivity and fatigue resistance at low temperatures; in the present invention, Nd 3+ The electron transition of the 4f shell (also called ff transition) has near-infrared photoluminescence characteristics. 3+ The ions are activators of near-infrared luminescence, which is the main reason for the luminescence of the compound.
[0024] Switchable physical / chemical properties are the main features of stimulus-responsive or smart materials. As one of the basic components in the electrical and electronic industries, dielectric materials are widely used as capacitors. Dielectric materials with low or high dielectric constants ε' are very important as they act as ultra-low dielectrics in integrated circuits and as high dielectrics in energy storage and device miniaturization. However, responsive dielectrics with switchable dielectric constants are less explored. Switchable dielectric constants, i.e., dielectric transitions between low and high dielectric states, enrich the family of dielectric materials and will find applications in smart devices as switches, sensors, actuators, etc.
[0025] The present invention utilizes the characteristics of phase change materials to design and synthesize a 3D structural model, and introduces rare earth ions to give the material luminescence properties. The materials constructed by the present invention make the types of phase change materials more diverse, which is conducive to making the material's luminescence properties better through different rare earth ions. Phase change materials also have many excellent properties: dielectric switching, piezoelectricity, pyroelectricity, ferroelectricity, etc.
[0026] The present invention first proposed and synthesized (MQ)5[K2Nd2(NO3) 13 ] compounds. The entire synthesis and preparation process is relatively simple, which is conducive to reducing costs and is suitable for industrial needs. The compounds of the present invention are compounds with dielectric properties and NIR luminescence properties. Compared with existing compounds with similar characteristics, the high-multiple dielectric response caused by the ordered-disordered structural phase transition of the compounds can still have dielectric sensitivity and fatigue resistance at low temperatures; rare earth ions have rich 4f energy levels and unique electronic configurations, which can partially or completely replace lead ions and reduce environmental pollution. At the same time, the compounds of the present invention have the following advantages over traditional optoelectronic materials: 1. Compared with rare earth complexes, the perovskite in the present invention is an inorganic compound with good thermal stability and good thermoluminescence efficiency; 2. Compared with pure organic optoelectronic materials, it is cheap, has high color purity (narrow emission peak), and is complicated to synthesize; 3. Compared with traditional perovskites, it has no lead pollution.
[0027] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:
[0028] (1) The present invention synthesizes a novel compatible dielectric transition and near-infrared (NIR) luminescent material, and the obtained compound has good dielectric properties and luminescent properties at the same time.
[0029] (2) The novel bimetallic perovskite structure A synthesized by the present invention 2.5 B I B III X 6.5 The compound exhibits a clear dielectric transition between the low state and the high state in the temperature range of 130K~240K, corresponding to the order-disorder structural phase transition.
[0030] (3) The preparation process of the present invention is relatively simple, with high atomic utilization, which solves the problems of the complex synthesis process of common perovskites, and has high yield and high sample purity. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The present invention (MQ) 5 [K2Nd2 (NO3) 13 ] schematic diagram of the crystal stacking structure at 153K;
[0032] Figure 2 The present invention (MQ) 5 [K2Nd2 (NO3) 13 ] schematic diagram of the crystal stacking structure at 300K;
[0033] Figure 3 The present invention (MQ) 5 [K2Nd2 (NO3) 13 ] X-ray powder diffraction pattern;
[0034] Figure 4 For the sample (MQ)5[K2Nd2(NO3) in the embodiment of the present invention 13 ] is a schematic diagram of the DSC curve measured during the hot and cold cycle;
[0035] Figure 5 The present invention (MQ) 5 [K2Nd2 (NO3) 13 ] schematic diagram of the switchable ε′-T curve;
[0036] Figure 6 The present invention (MQ) 5 [K2Nd2 (NO3) 13 ]'s ε' switching period diagram at 1 MHz, and the dielectric properties of the compound were determined by polycrystalline samples;
[0037] Figure 7 The present invention (MQ) 5 [K2Nd2 (NO3) 13 ]’s UV absorption spectrum;
[0038] Figure 8The present invention (MQ) 5 [K2Nd2 (NO3) 13 ]’s UV absorption spectrum fitting band gap diagram;
[0039] Figure 9 The present invention (MQ) 5 [K2Nd2 (NO3) 13 ] excitation and emission spectra;
[0040] Figure 10 The present invention (MQ) 5 [K2Nd2 (NO3) 13 ]’s fluorescence decay curve. DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be further described below with reference to the accompanying drawings.
[0042] Unless otherwise specified, the materials and reagents used in the following examples are all commercially available. Experimental methods without specific conditions specified in the examples are generally performed under conventional conditions or the conditions recommended by the manufacturer.
[0043] X-ray powder diffraction (XRD) analysis was carried out on a SmartLab SE X-ray diffractometer from Rigaku Corporation.
[0044] PL excitation spectra, PL emission spectra, and PL decay curves were performed on an FLS980 spectrometer (Edinburgh) equipped with a continuous xenon lamp (450 W), a pulsed flash lamp, and a 345 nm picosecond pulse laser.
[0045] X-ray single crystal diffraction was performed on a Rigaku XtLAB Synergy R single crystal diffractometer using a Mo target and a Kα radiation source (λ = 0.071073 nm) at room temperature (~301 K). The structure was elucidated using Olex2.
[0046] Raw materials: Quinuclidine HQ (97%, J&K Technologies, CAS: 100-76-5), CHI (99%, Aladdin, CAS: 74-88-4), Nd(NO) 6H O (99.9%, Adamas, CAS: 16454-60-7), KCl (99.99%, Aladdin, CAS: 7447-40-7), HNO (65.0%), deionized water, ethyl acetate (99.5%, Fuchen Chemical, CAS: 141-78-6). All chemicals were used as received and did not require special treatment.
[0047] Example 1
[0048] (MQ)5[K2Nd2(NO3) 13Sample preparation
[0049] Mix 5 mol of quinuclidine and 6 mol of CHI, react at room temperature for one day in 50 mL of ethyl acetate as solvent, and filter the product to obtain a white powder solid. Dry it in a 60°C oven for 30 min, then take it out and add 10 mmol of concentrated nitric acid to oxidize the I ions in the product to I elemental substance. Heat it on a 90°C hot plate to sublimate the I elemental substance until the solution is clear and transparent to obtain MQ.
[0050] 5mmol MQ, 2mmol Nd(NO3)3·6H2O, and 2mmol KCl were dissolved in 25mL of deionized water. The mixture was mixed and then stirred evenly with 5mmol of concentrated nitric acid. Finally, 10mL of deionized water was added to reduce the crystal precipitation rate and improve the crystal quality. The mixture was placed on a 40℃ hot plate to grow crystals. After about 2-3 days, light purple single crystals were precipitated. The mixture was collected and dried to obtain (MQ)5[K2Nd2(NO3) 13 ], yield 71.8%.
[0051] The compound was characterized by X-ray single crystal diffraction and the (MQ)5[K2Nd2(NO3) 13 The results show that MQ (N-methylquinuclidine cation) is positive monovalent; neodymium (Nd) is positive trivalent; potassium (K) is positive monovalent; and nitric acid (HNO3) is negative monovalent. The (MQ)5[K2Nd2(NO3)] was analyzed at 153K and 300K respectively. 13 ] conducted X-ray single crystal diffraction experiments. At 153K, it belongs to the monoclinic space group P21 / n, and the cell parameters β=93.6825(18)°. At 300K, it crystallizes in the monoclinic space group P2 / m with unit cell parameters of β=101.914(4)°。
[0052] The crystal structure of the compound was obtained by single crystal X-ray diffraction at 153K. Figure 1 (a) shows a schematic diagram of the crystal stacking structure. The crystal belongs to P21 / n space group; Figure 1 (b) is a simplified diagram of the basic asymmetric unit; Figure 1 (c) Figure 1 Schematic diagram of ring A shown in (b); Figure 1 (d) Figure 1 (b) Schematic diagram of the B ring shown.
[0053] At 300K, such as Figure 2 (a) shows a schematic diagram of the crystal stacking structure, and the crystal belongs to the P2 / m space group; Figure 2 (b) is a simplified diagram of the basic asymmetric unit; Figure 2 (c) Figure 2 Schematic diagram of ring A shown in (b); Figure 2 (d) Figure 2 (b) Schematic diagram of the B ring shown.
[0054] The XRD diffraction pattern of the compound powder is as follows Figure 3 As shown in the figure, the theoretical XRD diffraction pattern obtained by simulating its crystal structure is as follows: Figure 3 Below is the sample simulation peak. The diffraction peak positions of the compounds are consistent, indicating that the obtained samples are all pure phases. It is worth noting that as the doping concentration increases, the diffraction peak shifts to the left.
[0055] Example 2
[0056] (MQ)5[K2Nd2(NO3) 13 ]Dielectric response characterization
[0057] On the Tonghui TH2828A analyzer, the frequency is 500Hz~1000kHz, the temperature is 135~240K, and the rate is 10Kmin -1 Under the conditions of , the dielectric constant ε (ε=ε′~ε″, ε′ and ε″ represent the real and imaginary parts respectively) is measured to be 1. The voltage applied in the measurement is 1V. At 1000kHZ, the initial dielectric constant of 1 is about 5. During the heating process, the ε value increases steadily, such as Figure 5 As shown in Figure 2, it reaches a peak value of 8.3 at around 190K and remains relatively stable when further heated. The ε curve after cooling is similar to that during heating ( Figure 4 In the measurement temperature range of 135-240K, the DSC curve of the compound showed a pair of abnormal peaks when heated at around 190K and cooled at around 175K ( Figure 4 ), indicating that a phase transition occurs within the temperature range. This further proves the dielectric response. Figure 6 The figure shows the ε′ switching cycle diagram at 1000kHz. The dielectric stability of the compound was determined by polycrystalline samples. After 7 heating-cooling cycle tests, the dielectric constant of the sample can still maintain a good on-off response with the change of temperature. max / ε' min The ratio is as high as 1.88, ε' max As high as 1.18 times that of silicon nitride. In addition, at a frequency of 1MHz, after multiple ε' switching cycles, the dielectric constant is max and ε' min The reversibility of switching between them is not significantly weakened, which gives the material good thermodynamic stability.
[0058] Example 3
[0059] (MQ)5[K2Nd2(NO3) 13 ]Luminescence Photocharacterization
[0060] The luminescence properties of the compounds were tested. Figure 7 This is the ultraviolet absorption spectrum, and the strongest excitation peak is 597nm. Figure 8 The band gap diagram is fitted for the UV absorption spectrum, and the band gap is 2.96eV. Figure 9 The excitation and emission spectra of the compound are shown in Figure 2. The excitation wavelength is 1066 nm, and the strongest excitation peak is 597 nm. Figure 10 The fluorescence lifetime is 1.920 μs. Examples 2 and 3 above demonstrate that the material prepared by the present invention exhibits both dielectric response and NIR luminescence properties, effectively addressing dielectric switchability during temperature changes while maintaining excellent fatigue resistance, enriching the family of dielectric materials. Furthermore, luminescence properties can be achieved in the near-infrared region. These characteristics enable the compounds of the present invention to be used in smart devices as dielectric switches, sensors, actuators, and the like.
Claims
1. A NIR luminescent nitrate-bridged bimetallic dielectric material with switchable dielectric constant, characterized in that: The NIR luminescent nitrate-bridged bimetallic dielectric material mainly includes a structural formula of (MQ)5[K2Nd2(NO3) 13 ], wherein MQ (N-methylquinuclidine cation) is monovalent, Nd (neodymium) is trivalent, K (potassium) is monovalent, NO3 - The valence state of (nitrate) is negative one.
2. The dielectric constant switchable NIR luminescent nitrate-bridged bimetallic dielectric material according to claim 1, wherein the basic physical feature is that the compound is a light purple bulk crystal.
3. The NIR luminescent nitrate-bridged bimetallic dielectric material with switchable dielectric constant according to claim 1, characterized in that: The compound belongs to the monoclinic space group P21 / n at 153K, and the cell parameters β=93.6825(18)°; at 300K, it crystallizes in the monoclinic space group P2 / m, with unit cell parameters of β=101.914(4)°.
4. The NIR luminescent nitrate-bridged bimetallic dielectric material with switchable dielectric constant according to claim 1, characterized in that: The dielectric constant of the compound can switch between high and low states within the temperature range of 130K to 240K, corresponding to an ordered-disordered structural phase transition; it also emits near-infrared light at 1068nm, with a fluorescence lifetime of 1.920μs; the material has the properties of dielectric response and NIR luminescence.
5. A method for preparing the NIR luminescent nitrate-bridged bimetallic dielectric material with switchable dielectric constant according to claim 1, characterized in that: The steps include: a) mixing quinuclidine and CH3I and reacting them in ethyl acetate as solvent, filtering, drying, adding concentrated nitric acid to oxidize the I ions in the product, heating and sublimating to remove the I ions, and obtaining MQ; b) mixing MQ, neodymium nitrate hexahydrate (Nd(NO3)3·6H2O), potassium chloride and nitric acid, and using deionized water as a solvent; c) heating the clear solution obtained in step b) to slowly evaporate the solvent, thereby obtaining the compound in the form of light purple block crystals.
6. The preparation method according to claim 5, characterized in that: Step b) Dissolve the MQ, Nd(NO3)3·6H2O and KCl in deionized water, mix and add nitric acid to evenly stir, finally add deionized water, place it on a hot plate to grow crystals, wait for about 2-3 days to precipitate light purple single crystals, collect and dry to obtain (MQ)5[K2Nd2(NO3) 13 ].
7. The preparation method according to claim 5, characterized in that: In step b), the molar ratio of MQ, Nd(NO3)3·6H2O, KCl and HNO3 is 5:2:2:
5.
8. Use of the dielectric switch type NIR luminescent nitrate bridged bimetallic dielectric material according to claim 1 in dielectric switch materials, sensors, actuators and capacitors with switchable dielectric response characteristics.
9. Use of the dielectric switch type NIR luminescent nitrate bridged bimetallic dielectric material according to claim 1 in NIR luminescent materials.
10. Use of the dielectric switch type NIR luminescent nitrate bridged bimetallic dielectric material according to claim 1 in information storage, data communication and optoelectronic devices.
Citation Information
Patent Citations
Rare earth europium nitrate complex luminescent material as well as preparation method and application thereof
CN115819441A
Organic-inorganic hybrid molecule-based material as well as preparation method and application thereof
CN118027043A